Student Preferences in Choosing Chemistry as an Elective Course in Phase F of the Merdeka Curriculum - Wella, Wella Aulia Putri; Andika, Andika Prasetya; Desi, Desi Handayani; Muktiningsih, Muktiningsih; Ridwan, Achmad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The Merdeka Curriculum differs from the 2013 curriculum regarding elective subjects. The Merdeka Curriculum has no more specialization groups such as science, social studies or language. Merdeka Curriculum allows students to choose elective subjects that suit their interests, talents and abilities when entering phase F at the Senior High School level. Schools must open at least seven elective subjects adjusted to the characteristics and human resources owned by the school. Chemistry is one of the elective subjects that students can choose in Phase F of the Merdeka Curriculum. This study aims to determine the factors that make students choose chemistry as their elective subject in Phase F of the Merdeka Curriculum. This research was conducted at SMA Negeri 17 Jakarta in the 2023-2024 academic year. The research subjects were students in chemistry specialization classes: XI-A Chemistry and XI-B Chemistry. This research uses a qualitative method with a case study research type. Sampling in this study used a purposive sampling technique with certain considerations. Sampling in this study used a purposive sampling technique with certain considerations. Data collection techniques were carried out through interviews with nine students in chemistry specialization classes, and the data obtained were analyzed qualitatively with stages, namely data reduction, conclusions, and verification. The results showed that intrinsic and extrinsic factors influence students' tendency to choose chemistry as their chosen subject. Intrinsic factors include interest in chemistry, academic value, and future study or career plans. Intrinsic factors influencing students most are future study or career plans and individual interest in chemistry. In contrast, extrinsic factors include family factors, friend factors, teacher factors, and support from schools. The extrinsic factor that most influences students is the teacher factor.